2018
DOI: 10.3390/s18030928
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impact of Poly(3-hexylthiophene) Chain Length and Other Applied Side-Chains on the NO2 Sensing Properties of Conducting Graft Copolymers

Abstract: The detection and concentration measurements of low concentrations of nitrogen dioxide (NO2) are important because of its negative effects on human health and its application in many fields of industry and safety systems. In our approach, conducting graft copolymers based on the poly(3-hexylthiophene) (P3HT) conducting polymer and other side-chains, polyethylene glycol (PEG) and dodec-1-en, grafted on a poly(methylhydrosiloxane) backbone, were investigated. The grafts containing PEG (PEGSil) and dodec-1-en (Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The response of sensors using the two copolymers to NO 2 concentrations in the range of 200-1000 ppb is shown in (Figure 5) with the solid lines. Based on the observed result, SilPEG is much more sensitive to NO 2 than DodecSIL, which is in line with the results of our previous investigations [11]. The same sensing experiments were repeated under UV light activation (Figure 5 dashed lines).…”
Section: Nitrogen Conditionssupporting
confidence: 90%
See 1 more Smart Citation
“…The response of sensors using the two copolymers to NO 2 concentrations in the range of 200-1000 ppb is shown in (Figure 5) with the solid lines. Based on the observed result, SilPEG is much more sensitive to NO 2 than DodecSIL, which is in line with the results of our previous investigations [11]. The same sensing experiments were repeated under UV light activation (Figure 5 dashed lines).…”
Section: Nitrogen Conditionssupporting
confidence: 90%
“…In our previous work [11], a comprehensive study of NO 2 sensing properties of different graft co-polymers containing regioregular poly(3-hexylthiophene) (rr-P3HT) was presented. The investigation was conducted for NO 2 concentrations in the low ppm range (1-20 ppm) in nitrogen (carrier gas) and at multiple temperatures, from room temperature (RT) up to 100 • C. The noticeable problem shown in the mentioned work was poor stability and a strong baseline drift at RT.…”
Section: Introductionmentioning
confidence: 99%
“…PPy thin film RT 36 @ 100 ppm 10 3 2170 @ 100 ppm [49] 15-layers PANI film RT 65 @ 20 ppm 20 nr nr [64] PT film 60 400 @ 1000 ppm 100 nr nr [65] PT thin film RT 33 @ 100 ppm 10 3 220 @ 100 ppm [66] Interconnected nanofibrous PT thin film RT 48 @ 100 ppm 25 4 80 @ 100 ppm [67] PEDOT nanotubes RT 52 @ 63 ppm 0.2 2 nr [51] PANI thin film RT 11 @ 10 ppm 10 nr 420 @ 100 ppm [68] Ag-PPy RT 68 @ 100 ppm 5 nr 1777 @ 50 ppm [69] PANI-fibers RT 80 @ 1 ppm 1 6 63 @ 500 ppm [16] PEDOT film 80 22 @ 100 ppm 10 nr nr [50] PEDOT-rGO 80 7 @ 100 ppm 1 5 nr [70] DBSA-doped PPy-WO 3 RT 71 @ 100 ppm 5 3 5990 @ 100 ppm [71] PPy-NiO RT 47 @ 100 ppm 10 4 1500 @ 60 ppm [72] PPy-Fe 2 O 3 nanorod RT 12 @ 50 ppm 1 5 nr [73] PT-WO 3 90 500 @ 100 ppm 10 nr nr [74] PT-SnO 2 90 400 @ 100 ppm 10 nr nr [75] rrP3HT-PMS Graft 50 2300 @ 5 ppm 5 3 nr [76] PEGSil-H 50 900 @ 5 ppm 1 Nr nr [77] IM-0.1/P-1.0 60 240 @ 1 ppm 0.1 15 228 @ 1 ppm This Study methods of sensor measurements. The XPS data of three different samples were mainly discussed through the N 1s spectra, as no distinct changes were observed in O 1s and C 1s spectra.…”
Section: Sensing Element Sensing Temperature [°C] Sensitivity [%] Lod...mentioning
confidence: 99%
“…They also indicated that alkyl side chains promoted carrier mobility while PEG side chains did not. Two earlier papers 34,35 demonstrated that graft copolymers with small amounts of PEG side chains improved sensor response due to their interaction with NO 2 .…”
Section: Introductionmentioning
confidence: 99%